Inter-Annual and Geographical Variations in the Extent of Bare Ice and Dark Ice on the Greenland Ice Sheet Derived from MODIS Satellite Images - Shimada, Rigen; Takeuchi, Nozomu; Aoki, Teruo (Frontiers in Earth Science, 2016)
Areas of dark ice have appeared on the Greenland ice sheet every summer in recent years. These are likely to have a great impact on the mass balance of the ice sheet because of their low albedo. We report annual and geographical variations in the bare ice and dark ice areas that appeared on the Greenland Ice Sheet from 2000 to 2014 by using MODIS satellite images. The July monthly mean of the extent of bare ice showed a positive trend over these 15 years, and large annual variability ranging from 89,975 km2 to 279,075 km2, 5% and 16% of the entire ice sheet, respectively. The extent of dark ice also showed a positive trend and varied annually, ranging from 3,575 km2 to 26,975 km2, 4% and 10% of the bare ice extent. These areas are geographically varied, and their expansion is the greatest on the western side, particularly the southwestern side of the ice sheet. The bare ice extent correlates strongly with the monthly mean air temperature in July, suggesting that the extent was determined by snow melt. The dark ice extent also correlates with the air temperature; however, the correlation is weaker. The dark ice extent further correlates negatively with solar radiation. This suggests that the extent of dark ice is not only controlled by snow melt on the ice, but also by changes in the surface structures of the bare ice surface, such as cryoconite holes, which are associated with impurities appearing on the ice surface.